(untitled) (Biological Sciences - PJSIR, 2005)
The study reports some preliminary observations on the occurence of Fusarium head scab (FHS) disease on wheat under natural conditions. These studies were conducted in nursery trials on the wheat varieties of national and international origin prior to their release for cultivation in Pakistan. During the test trial on 1471 nursery entries, covering varities of international origin for early and advanced screening, the candidate varities for national wheat programme, and the commercial varieties, all were noted to show 16% to 59% susceptibility to FHS. These observations have been identified as significant indicators for giving FHS the due status in the national wheat disease programmes, before approving the release of new wheat varieties for farm the field level cultivation